Conserving marine biodiversity in areas beyond national jurisdiction: co-evolution and interaction with the law of the sea - Warner, Robin M. (Frontiers in Marine Science, 2014)
As global shipping intensifies and technological advances provide more opportunities to access the resources of the high seas and the deep seabed beyond national jurisdiction (ABNJ), the catalogue of threats to the marine environment and its biodiversity increase commensurately. Beyond these threats, new and emerging uses of ABNJ including more intrusive marine scientific research, bio-prospecting, deep seabed mining and environmental modification activities to mitigate the effects of climate change have the potential to harm the highly interconnected and sensitive ecosystems of the open ocean and the deep seabed if not sustainably managed now and into the future. Modern conservation norms such as environmental impact assessment, marine protected areas, marine spatial planning and development mechanisms such as technology transfer and capacity building are under developed in the legal and institutional framework for ABNJ. This article examines key normative features of the legal and institutional framework for ABNJ and their applicability to conservation of marine biodiversity, gaps and disconnects in that framework and ongoing global initiatives to develop more effective governance structures. It discusses some of the options being considered in the UN Ad Hoc Informal Open-ended Working Group to study issues related to the conservation and sustainable use of marine biodiversity in areas beyond national jurisdiction (BBNJ Working Group) to evolve the legal and institutional framework for conservation and sustainable use of marine biodiversity in ABNJ and their current and future relevance for the law of the sea. It concludes that the discussions in the BBNJ Working Group and related initiatives in the Convention on Biological Diversity (CBD) and at regional level have demonstrated that a more integrated legal and institutional structure is needed to address growing threats to marine biodiversity in ABNJ.